2021
DOI: 10.9778/cmajo.20210161
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric primary care in Ontario and Manitoba after the onset of the COVID-19 pandemic: a population-based study

Abstract: Primary health care is essential to maintaining the health of individuals and populations, and the functioning of a health care system. For children in particular, primary care is the cornerstone for monitoring growth and development, providing anticipatory guidance and delivering vaccinations for vaccine-preventable diseases. A good primary care system is associated with more equitable health in populations. 1,2 Delays in or failure to access regular and timely primary care can lead to service gaps during a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“… 32 , 33 Similarly, disproportionate reductions in primary care during the pandemic have also been reported for migrant children in Ontario, Canada. 34 Focusing on middle adulthood, evidence prior to this study showed that migrant women experience challenges in accessing maternity care in the UK. 35 Gender-stratified analysis based on this a-priori hypothesis should be conducted in future in migrants of child-bearing age.…”
Section: Discussionmentioning
confidence: 86%
“… 32 , 33 Similarly, disproportionate reductions in primary care during the pandemic have also been reported for migrant children in Ontario, Canada. 34 Focusing on middle adulthood, evidence prior to this study showed that migrant women experience challenges in accessing maternity care in the UK. 35 Gender-stratified analysis based on this a-priori hypothesis should be conducted in future in migrants of child-bearing age.…”
Section: Discussionmentioning
confidence: 86%
“…Healthcare seeking between waves and in other states of the country may have continued quite similarly to the years before COVID-19 [ 29 , 51 , 53 ]. Furthermore, similar to other developed countries [ 54 , 55 , 56 ], Australia has provisioned telehealth services during the COVID-19 pandemic [ 30 ], and this might have enabled care seeking to be similar to pre-pandemic [ 29 ]. Other researchers have also studied the issue of healthcare avoidance during COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by our finding that ‘Child Problems’, which addresses behavioural, cognitive and social problems that a child may be experiencing,23 was the highest endorsed PAT subscale, and was even higher than Verma et al found. The pandemic led to a suspension of primary care visits, which created gaps in healthcare for CMC 27 28. These visits also provide important opportunities for primary care physicians to monitor behavioural development and offer appropriate interventions.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, the COVID-19 pandemic resulted in the decreased provision of home care and supportive care services (eg, physiotherapy, occupational therapy, etc) as well as reduced access to in-person healthcare appointments 3 7 28. In turn, there was likely an increased demand placed on parents to fill in the care gaps created by the suspension of these health services.…”
Section: Discussionmentioning
confidence: 99%